District governments in Madhya Pradesh: Innovative initiatives for decentralisation of governance (Note) - Behar, Amitabh (2000)
Author presents the conceptual framework of District Government (DG) and contexualises it in the decentralisation process which is underway in Madhya Pradesh. Assessing efficacy of DG in the light of criticism, he attempts to generate a debate on DG amongst academics, development professional and activists, NGOs and government functionaries to facilitate proper comprehension of this significant institutional change, which, according to the author, has largely gone unnoticed. - Reproduced
Keywords: Note; Decentralization - India - Madhya Pradesh; District administration - India - Madhya Pradesh; District administration